Sensitivity analysis of transient bioheat transfer with perfusion rate dependent on tissue injury - Jasiński, Marek (Computer Assisted Methods in Engineering and Science, 2009)
The sensitivity analysis of transient temperature field in the tissue domain with respect to its thermophysical parameters is discussed. In particular, the influence of tissue specific heat, thermal conductivity, perfusion rate and metabolic heat source on the temperature distribution is considered. In order to determine the influence of variations of these parameters on temperature distribution the direct approach of sensitivity analysis is applied. Perfusion rate is treated as dependent on tissue injury which is estimated on the basis of Arrhenius integral. On the stage of numerical realization the boundary element method is used. In the final part of paper the results obtained are shown.